STUDY OF THE LONG-TERM STABILITYOF ADSORPTION-SEMICONDUCTOR SENSORS FOR HYDROGEN: UDC 543.272.2 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
Stability of 32 adsorption semiconductor sensors based on SnO2 with additions Sb and Pd of different concentration was studied. It was established that the sensors didn't lose their sensitivity towards H2 during 9 months of their long-term operation. A change of the sensor signal was in the range of ±10 % for all sensors practically if a periodical calibration was applied
Keywords: -